Nanozymes in Tumor Theranostics - Ma, Qiulian; Liu, Yanfang; Zhu, Haitao; Zhang, Lirong; Liao, Xiang (Frontiers in Oncology, 2021)
Nanozyme, a newly generation of enzyme mimic, has recently attracted great attention. Nanozymes could catalyze chemical reactions as biological enzymes under physiologically mild conditions with high-efficiency catalytic activity. Moreover, nanozymes overcome the shortcomings of natural enzymes, such as the easy inactivation, high cost and low yield. With the development of more and more smart and multi-functional nano-systems, nanozymes displayed great achievement in tumor biology. In this review, we outline the latest advances of nanozymes in tumor and tumor microenvironment diagnosis, therapy and theranostics.